Heritage interaction, museum communication and learning (Cadernos de Sociomuseologia, 2014)
In this article, we want to present some reflections about education and communication in nowadays museums, which ones make efforts to provide education to its public. The question is: which education and to who are they talking about? To students? Or about Patrimonial Education, aiming to the autonomy of different public categories, with emphasis in learning through experiences, leisure and many others intermediated through communication? There are educative proposals in museums. It lacks to segment the actions to qualify the programs. The preconceived ideas that education is only for children, among others, keeps away adults and young people from museums. Besides it, society in undeveloped contries lacks of opportunity of leisure, entertainment and learning. The collective patrimonies that museums shelter need to be better shared with a diverse public, as diverse is the brazilian and Rio Grande do Sul’s society. Keywords: patrimony, museology, learning, communication, public.